Difunctional composite electrocatalyst with NiFe nanoparticles coated with carbon layer as well as preparation method and application of difunctional composite electrocatalyst
By preparing a dual-function composite electrocatalyst with a carbon layer coated with NiFe nanoparticles in a metal-air battery, the problems of scarce resources and poor stability of precious metal catalysts are solved, efficient oxygen reduction and oxygen evolution reaction are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411863839.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing precious metal catalysts (such as Pt, Ru, Ir) in metal-air batteries have limited their large-scale use in industrial applications due to scarce resources, high prices and poor stability. At the same time, non-precious metal catalysts perform poorly in catalytic redox reactions (ORR) and oxygen evolution reactions (OER), and are difficult to replace precious metal catalysts.
Fe-N-C material was prepared by self-assemblying dimethylimidazole, zinc salt and iron salt in an organic solvent to form a transition metal organic framework compound and heat treatment in a protective atmosphere. Then, the Fe-N-C material is microwave-heated with the precursor of nickel and iron to form a dual-function composite electrocatalyst with a carbon layer coated with NiFe nanoparticles.
This dual-function composite electrocatalyst exhibits high activity in oxygen reduction and oxygen evolution reactions, and can effectively replace precious metal catalysts, reduce production costs, and improve the stability of the catalyst.
Smart Images

Figure CN119695177A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst and a preparation method and application thereof. Background Art
[0002] With the energy crisis caused by the continuous depletion of fossil fuels and the increasingly prominent environmental problems caused by the excessive consumption of fossil fuels, it is urgent to seek and develop a clean, efficient and sustainable energy supply system. Among them, renewable energy will become an important part of the future energy structure. Rechargeable air batteries have important application value in the future energy utilization and energy storage fields due to their high theoretical energy density, low cost and safety. The charge and discharge reactions on the air cathode of the air battery are: The oxygen reduction reaction (ORR) moves to the right during discharge, and the oxygen evolution reaction (OER) moves to the left during charge. The catalysts for these two reactions (ORR and OER) are key components of the cathode of rechargeable metal-air batteries. However, both ORR and OER are complex 4e - The coupled reaction, whose slow kinetics limit the overall energy conversion efficiency of metal-air batteries. Therefore, developing high-performance ORR and OER electrocatalysts and promoting their conversion efficiency are crucial to the development of metal-air batteries. At present, Pt-based catalysts based on precious metal materials are considered to be the most ideal ORR catalysts, and Ru and Ir-based catalysts are the most effective OER catalysts, but the scarce resources, high prices and poor stability of these precious metal catalysts seriously hinder their large-scale application in industry. Therefore, designing and developing a cheap and efficient non-precious metal, bifunctional catalyst to replace the precious metal Pt, Ru and Ir-based catalysts is of great significance to promote the commercialization process and practical application of air batteries.
[0003] Among many non-precious metal catalysts, transition metal-nitrogen doped carbon-based (MNC) ORR catalysts have attracted extensive attention from domestic and foreign research institutions due to their high catalytic efficiency, good stability and low cost. In recent years, the application of MNC catalysts in ORR has made important progress. For example, Dodelet et al. (M. Lefevre et al., Science, 2009, 324.) prepared a highly active Fe-NC catalyst by pyrolyzing a precursor composed of o-phenanthroline, iron salt and zeolite imidazolate framework material. The catalytic performance is close to that of commercial Pt / C catalysts, indicating that non-precious metal ORR catalysts have made great progress in activity and stability. In 2011, Wu et al. (G. Wu et al., Science, 2011, 332.) used polyaniline (PANI) coated carbon black and transition metal salts as precursors to prepare a highly active PANIFeCo-C catalyst by pyrolysis. Its ORR catalytic performance is close to that of Pt-based ORR catalysts. Zhao et al. (J. Mater. Chem. A, 2016, 4, 3858) used o-phenylenediamine coated carbon black and ferric chloride as precursors, and obtained Fe-Nx / C-1 catalyst after pyrolysis. Its oxygen reduction activity was even higher than that of commercial Pt / C catalyst under alkaline conditions. Guan et al. (Z. Guan. et al., Chem. Commun., 2018, 54, 12073) used poly-o-phenylenediamine as raw material, silica colloid as template, and ammonium persulfate and ferric chloride as initiator and dopant to obtain the polymer as precursor. After pyrolysis, Fe, S, N co-doped carbon (m-FeSNC) ORR catalyst was obtained, which was used in zinc-air batteries with a peak power density of 0.22W / cm -2 , which performs better than Pt / C catalysts. However, the catalytic performance of this type of MNC catalysts for OER is not ideal.
[0004] In fact, as early as 1952, Edison and Jungner discovered the poisoning effect of Fe impurities on nickel-based alkaline batteries (RL Tichenor, Ind. Eng. Chem. 1952, 44, 973.). Later studies have shown that NiFe alloy (especially Ni3Fe) is an extremely effective OER catalyst. After the metal Ni is converted into NiOOH through activation treatment, it accelerates the absorption of OH - The species is oxidized to molecular oxygen, and the electronic structure of the catalyst is adjusted by coupling with iron, which significantly improves the catalytic activity of OER (X. Zhang, et al., ACS Catal. 2015, 6, 580.), but NiFe alloy has no activity for ORR, which affects its wide application. Summary of the invention
[0005] The object of the present invention is to provide a carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst and a preparation method and application thereof, wherein the bifunctional composite electrocatalyst has high oxygen reduction (ORR) and oxygen evolution reaction (OER) activities.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst, comprising the following steps:
[0008] Dimethylimidazole, zinc salt, iron salt and organic solvent are mixed and self-assembled to obtain a transition metal organic framework compound;
[0009] The transition metal organic framework compound is subjected to heat treatment in a protective atmosphere to obtain a Fe-NC material;
[0010] The Fe-NC material is physically mixed with an iron precursor and a nickel precursor, and then subjected to microwave heating to obtain a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst.
[0011] Preferably, the iron salt includes ferric ammonium sulfate, ferrous sulfate heptahydrate, ferric chloride or ferric chloride hexahydrate; and the zinc salt includes zinc nitrate hexahydrate.
[0012] Preferably, the molar ratio of dimethylimidazole, zinc salt and iron salt is 30:8:1-5.
[0013] Preferably, the self-assembly temperature is 20-35° C. and the time is 24-36 hours.
[0014] Preferably, the heat treatment temperature is 900-1000° C. and the time is 2-4 hours.
[0015] Preferably, the iron precursor includes iron acetylacetonate or iron dodecacarbonyl; the nickel precursor includes nickel acetylacetonate or nickel chloride.
[0016] Preferably, the usage ratio of the Fe-NC material, the iron precursor and the nickel precursor is 30-40 mg: 30 mmol: 60-90 mmol.
[0017] Preferably, the microwave heating time is 10 to 60 seconds; the microwave heating is performed under a protective atmosphere, and the gas used in the protective atmosphere includes nitrogen or argon.
[0018] The present invention provides a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst prepared by the preparation method described in the above technical solution.
[0019] The present invention provides the use of the carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst described in the above technical solution as a cathode material for a metal-air battery.
[0020] The present invention provides a method for preparing a carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst. The present invention uses dimethyl imidazole and a transition metal salt to synthesize a transition metal organic framework compound with a specific morphology and size, and then pyrolyzes to prepare a nitrogen-doped carbon material (Fe-NC) containing transition metal iron with a specific morphology, and the Fe-NC material is mixed with a nickel precursor and an iron precursor to obtain a carbon layer coated NiFe nanoparticle composite bifunctional electrocatalyst under microwave heating conditions. The preparation principle of the present invention is: under the action of a microwave field, the iron and nickel precursors are quickly reduced to NiFe nanoparticles; at the same time, the local high temperature generated by microwave heating causes the carbon material to interact strongly with the NiFe nanoparticles, so that the NiFe nanoparticles are coated with a carbon layer. The present invention loads NiFe alloy nanoparticles with high OER activity onto a Fe-NC carbon carrier with high ORR activity, thereby preparing a bifunctional composite electrocatalyst with high oxygen reduction (ORR) and oxygen evolution reaction (OER) activity, which can be used as a cathode catalyst in metal-air batteries.
[0021] Compared with the prior art, the present invention has the following advantages or positive effects:
[0022] The present invention is the first to use simple microwave heating technology to efficiently and quickly prepare a highly active bifunctional composite catalyst for use in metal-air batteries.
[0023] The present invention rapidly reduces the precursors of nickel and iron to NiFe nanoparticles under a microwave field, and simultaneously realizes the carbon layer coating the NiFe particles. Compared with the prior art, the reduction time of NiFe nanoparticles is extremely short, and the strong interaction between NiFe nanoparticles and the surface of Fe-NC materials forms a core-shell structure of the carbon layer coating the NiFe nanoparticles, which can effectively protect the NiFe nanoparticles from dissolving in the electrolyte and improve the stability of the catalyst.
[0024] The present invention adopts stable and low-cost dimethylimidazole, as well as low-cost and earth-abundant transition metal salts and transition metal organic precursors as raw materials to replace precious metals (Pt, Ru, Ir), so that the cost of raw materials used in the entire preparation process is low and the cost of catalysts can be significantly reduced.
[0025] The method of the invention is simple and efficient, the raw materials used are easily available and low in cost, the preparation process is simple, the requirements on equipment are low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a SEM image of the transition metal organic framework compound prepared in Example 1 of the present invention;
[0027] Figure 2 This is a SEM image of the iron-nitrogen-doped carbon material (Fe-NC) prepared in Example 1 of the present invention;
[0028] Figure 3 A comparison of the LSV polarization curves of ORR and OER of the Fe-NC material prepared in Example 1 of the present invention in an O2-saturated 0.1M KOH solution with commercial Pt / C (20wt.% Pt) and commercial RuO2 catalysts (Pt / C-RuO2);
[0029] Figure 4 The SEM image (a) and the corresponding backscattered electron scanning electron microscope image (BS-SEM, b) of the Fe-NC@NiFe-1 catalyst in Example 1 of the present invention;
[0030] Figure 5 TEM (a) and HR-TEM (b) images of the Fe-NC@NiFe-1 catalyst in Example 1 of the present invention;
[0031] Figure 6 This is a HR-TEM image of a single NiFe nanoparticle coated with a carbon layer in the Fe-NC@NiFe-1 catalyst in Example 1 of the present invention;
[0032] Figure 7 A comparison of LSV polarization curves of ORR / OER of Fe-NC, Fe-NC@NiFe-1 catalysts prepared in Example 1 of the present invention and commercial Pt / C-RuO2 catalysts in an O2-saturated 0.1M KOH solution;
[0033] Figure 8 A comparison of LSV polarization curves of ORR / OER of Fe-NC@NiFe-2 catalyst prepared in Example 2 of the present invention and commercial Pt / C-RuO2 catalyst in O2-saturated 0.1M KOH solution;
[0034] Fig. 9 A comparison of LSV polarization curves of ORR / OER of Fe-NC@NiFe-3 catalyst prepared in Example 3 of the present invention and commercial Pt / C-RuO2 catalyst in O2-saturated 0.1M KOH solution;
[0035] Fig.10 This is a comparison diagram of the LSV polarization curves of ORR / OER of the Fe-NC@NiFe-4 catalyst prepared in Example 4 of the present invention and the commercial Pt / C-RuO2 catalyst in an O2-saturated 0.1M KOH solution. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst, comprising the following steps:
[0037] Dimethylimidazole, zinc salt, iron salt and organic solvent are mixed and self-assembled to obtain a transition metal organic framework compound;
[0038] The transition metal organic framework compound is subjected to heat treatment in a protective atmosphere to obtain a Fe-NC material;
[0039] The Fe-NC material is physically mixed with an iron precursor and a nickel precursor, and then subjected to microwave heating to obtain a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst.
[0040] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0041] The invention mixes dimethylimidazole, zinc salt, iron salt and organic solvent to carry out self-assembly to obtain a transition metal organic framework compound.
[0042] In the present invention, the iron salt preferably includes ferric ammonium sulfate, ferrous sulfate heptahydrate, ferric chloride or ferric chloride hexahydrate; the zinc salt preferably includes zinc nitrate hexahydrate.
[0043] In the present invention, the molar ratio of dimethylimidazole, zinc salt and iron salt is preferably 30:8:1-5, more preferably 30:8:3-5.
[0044] In the present invention, the organic solvent is preferably methanol; the present invention has no special limitation on the amount of the organic solvent, which can be adjusted according to actual needs to ensure smooth reaction.
[0045] In the present invention, dimethylimidazole, zinc salt and iron salt are preferably dissolved in organic solvents respectively, the obtained three solutions are mixed, and self-assembly is performed under continuous stirring conditions.
[0046] In the present invention, the temperature of the self-assembly is preferably 20 to 35° C., more preferably 25 to 30° C., and the time is preferably 24 to 36 hours, more preferably 24 to 30 hours.
[0047] After completing the self-assembly, the present invention preferably centrifuges the obtained product, washes the obtained precipitate repeatedly with anhydrous ethanol for 3 times, transfers it into a vacuum drying oven at 80° C. and vacuum dries it for 12 hours, grinds the obtained product in a mortar for 20 to 30 minutes, and obtains a transition metal organic framework compound.
[0048] After obtaining the transition metal organic framework compound, the present invention performs heat treatment on the transition metal organic framework compound in a protective atmosphere to obtain the Fe-NC material.
[0049] In the present invention, the transition metal organic framework compound is preferably placed in a quartz boat and heat treated in a tube furnace.
[0050] In the present invention, the heat treatment temperature is preferably 900-1000°C, more preferably 950-1000°C, and the time is preferably 2-4h, more preferably 2-3h; the protective atmosphere preferably includes argon or nitrogen to obtain iron-nitrogen doped carbon material: recorded as Fe-NC material.
[0051] After obtaining the Fe-NC material, the present invention physically mixes the Fe-NC material with an iron precursor and a nickel precursor, and then performs microwave heating to obtain a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst.
[0052] In the present invention, the iron precursor preferably includes iron acetylacetonate or iron dodecacarbonyl; the nickel precursor includes nickel acetylacetonate or nickel chloride.
[0053] In the present invention, the usage ratio of the Fe-NC material, the iron precursor and the nickel precursor is preferably 30-40 mg:30 mmol:60-90 mmol, and more preferably 40 mg:30 mmol:90 mmol.
[0054] The present invention preferably places the iron precursor, the nickel precursor and the Fe-NC material in a mortar and grinds them for 20 to 30 minutes to mix them evenly, then puts them into a quartz bottle and passes a protective gas (Ar or N2) for 10 minutes to remove the residual air in the quartz bottle, and then places the quartz bottle in a microwave heating device for microwave heating to obtain a high-activity bifunctional composite electrocatalyst of carbon layer-coated NiFe nanoparticles.
[0055] In the present invention, the microwave heating time is preferably 10 to 60 seconds, more preferably 20 to 40 seconds, and further preferably 25 to 30 seconds; the microwave heating is preferably carried out under a protective atmosphere, and the gas used in the protective atmosphere preferably includes nitrogen or argon; the output power of the microwave equipment used for the microwave heating is preferably 700W, and the frequency is preferably 2.45GHz. The present invention has no special limitation on the microwave equipment used for the microwave heating, and any microwave oven known in the art can be used; in the embodiment of the present invention, it is specifically a Midea microwave oven with an output power of 700W and a frequency of 2.45GHz.
[0056] The present invention utilizes microwave heating to reduce Ni and Fe precursors under a microwave field to produce NiFe nanoparticles (2-5nm, Figure 5-6) is loaded onto the surface of Fe-NC material particles with high ORR activity, which can effectively avoid Ostwald ripening. At the same time, the strong interaction between NiFe nanoparticles and the surface of carbon materials under the microwave field causes the carbon layer to coat the NiFe nanoparticles to form a NiFe core-carbon shell (4-6 carbon layers) structure. The carbon shell can improve the durability of the catalyst by protecting the NiFe core from corrosion or shedding, which is original and innovative. Thus, a high-performance ORR and OER non-precious metal bifunctional carbon-based catalyst is prepared.
[0057] The present invention provides a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst prepared by the preparation method described in the above technical solution.
[0058] The present invention provides the application of the carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst as a cathode material for a metal-air battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0060] Example 1
[0061] (1) 30 mmol of dimethylimidazole, 8 mmol of zinc nitrate hexahydrate, and 5 mmol of ferrous sulfate heptahydrate were dissolved in 50 mL of methanol respectively, the three solutions were mixed, and the mixture was stirred at room temperature (25°C) for 24 h, and then centrifuged. The precipitate was washed three times with anhydrous ethanol, and then placed in a vacuum drying oven at 80°C for 12 h. The product was ground in a mortar for 20 min to obtain a transition metal organic framework compound.
[0062] (2) Weigh 500 mg of the transition metal organic framework compound of step (1) and place it in a quartz boat. Heat treat it in a tube furnace at 1000° C. for 2 h under Ar protection to obtain an iron-nitrogen doped carbon material (Fe-NC);
[0063] (3) Take 30 mmol of ferric acetylacetonate, 90 mmol of nickel acetylacetonate and 40 mg of the Fe-NC material obtained in step (2), grind them in a mortar for 30 min to mix them evenly, put them in a quartz bottle, pass Ar for 10 min to remove the residual air in the quartz bottle, and then put the quartz bottle in a microwave oven (Midea microwave oven, output power: 700 W, 2.45 GHz) for microwave heating for 20 s to obtain a bifunctional composite electrocatalyst, recorded as Fe-NC@NiFe-1.
[0064] Example 2
[0065] (1) 30 mmol of dimethylimidazole, 8 mmol of zinc nitrate hexahydrate, and 5 mmol of ferrous sulfate heptahydrate were dissolved in 50 mL of methanol respectively, the three solutions were mixed, and the mixture was stirred at room temperature (25°C) for 24 h, and then centrifuged. The precipitate was washed three times with 80% ethanol by mass, and then placed in a vacuum drying oven at 80°C for 12 h. The product was ground in a mortar for 20 min to obtain a transition metal organic framework compound.
[0066] (2) Weighing 500 mg of the transition metal organic framework compound of step (1) and placing it in a quartz boat under Ar protection, heat-treating it in a tube furnace at 1000° C. for 2 h to obtain an iron-nitrogen doped carbon material (Fe-NC);
[0067] (3) Take 30 mmol of ferric acetylacetonate, 90 mmol of nickel acetylacetonate and 40 mg of the Fe-NC material obtained in step (2), grind them in a mortar for 30 min to mix them evenly, put them in a quartz bottle and pass Ar for 10 min to remove the residual air in the quartz bottle, then put the quartz bottle in a microwave oven (Midea microwave oven, output power: 700 W, 2.45 GHz) and microwave heat them for 30 s to obtain a bifunctional composite electrocatalyst, recorded as Fe-NC@NiFe-2.
[0068] Example 3
[0069] (1) 30 mmol of dimethylimidazole, 8 mmol of zinc nitrate hexahydrate, and 5 mmol of ferrous sulfate heptahydrate were dissolved in 50 mL of methanol respectively, and then the three solutions were mixed, stirred continuously at room temperature (25°C) for 24 hours, and then centrifuged. The precipitate was repeatedly washed with anhydrous ethanol for 3 times, and then transferred to a vacuum drying oven at 80°C for 12 hours. The product was ground in a mortar for 20 minutes to obtain a transition metal organic framework compound;
[0070] (2) Weighing 500 mg of the organic metal framework compound obtained in step (1), placing it in a quartz boat under Ar protection, and heat treating it in a tube furnace at 1000° C. for 2 h to obtain an iron-nitrogen doped carbon material (Fe-NC);
[0071] (3) Take 30 mmol of ferric acetylacetonate, 90 mmol of nickel acetylacetonate and 30 mg of the Fe-NC material obtained in step (2), grind them in a mortar for 30 min to mix them evenly, put them in a quartz bottle and pass nitrogen for 10 min to remove the residual air in the quartz bottle, then put the quartz bottle in a household microwave oven (Midea microwave oven, output power: 700 W, 2.45 GHz) for microwave heating for 40 s to obtain a bifunctional composite electrocatalyst, recorded as Fe-NC@NiFe-3.
[0072] Example 4
[0073] (1) 30 mmol of dimethylimidazole, 8 mmol of zinc nitrate hexahydrate, and 5 mmol of ferrous sulfate heptahydrate were weighed and dissolved in 50 mL of methanol, and then the three solutions were mixed, stirred at room temperature (25°C) for 24 hours, and then centrifuged. The precipitate was repeatedly washed with anhydrous ethanol for 3 times, and then transferred to a vacuum drying oven at 80°C for 12 hours. The product was ground in a mortar for 20 minutes to obtain a transition metal organic framework compound;
[0074] (2) Weighing 500 mg of the transition metal organic framework compound obtained in step (1) and placing it in a quartz boat under Ar protection, heat-treating it in a tube furnace at 1000° C. for 2 h to obtain an iron-nitrogen doped carbon material (Fe-NC);
[0075] (3) 30 mmol of triiron dodecacarbonyl, 90 mmol of nickel acetylacetonate and 30 mg of the Fe-NC material obtained in step (2) were taken respectively, ground in a mortar for 30 min to mix evenly, placed in a quartz bottle and passed Ar for 10 min to remove the residual air in the quartz bottle, and then placed the quartz bottle in a household microwave oven (Midea microwave oven, output power: 700 W, 2.45 GHz) for microwave heating for 30 s to obtain a bifunctional composite electrocatalyst, recorded as Fe-NC@NiFe-4.
[0076] Characterization and performance testing
[0077] 1) Figure 1 This is a SEM image of the transition metal organic framework compound prepared in Example 1 of the present invention; it can be observed that these particles have a regular octahedral morphology, uniform particle size and good dispersibility.
[0078] 2) Figure 2 This is a SEM image of the iron-nitrogen doped carbon material (Fe-NC) prepared in Example 1 of the present invention; Figure 2 As shown, the particles still maintain the original octahedral structure, the particle size is uniform, the dispersion is good, and the particle size is 300-500nm.
[0079] 3) The ORR activity of the Fe-NC material prepared in Example 1 was compared with that of the commercial Pt / C (20 wt.% Pt) catalyst and the OER activity of the commercial RuO2 catalyst by electrochemical testing (LSV polarization curve test conditions: in an O2-saturated 0.1 M KOH solution, the rotation speed was 1600 rpm, and the scanning rate was 5 mV / s); the results are shown in Figure 3 .
[0080] Figure 3The LSV polarization curves of the Fe-NC material prepared in Example 1 of the present invention in an O2-saturated 0.1M KOH solution are compared with those of commercial Pt / C (20wt.% Pt) and commercial RuO2 catalysts (Pt / C-RuO2) for ORR and OER; Figure 3 It can be seen that the half-wave potential (E 1 / 2 =0.90 V) is significantly better than the half-wave potential (E 1 / 2 =0.86V). However, in the OER activity test, it can be seen that at 10mA / cm 2 (η 10 ) At the limiting current, the overpotential of the Fe-NC material is 0.77V, which is higher than the overpotential of the commercial RuO2 catalyst (0.38V), indicating that the OER performance is worse than that of RuO2. This shows that the Fe-NC material has a higher ORR activity than commercial Pt / C, but a lower OER activity than commercial RuO2. The ORR / OER potential difference (ΔE=E 10,OER -E 1 / 2,ORR )=1.1V, which is higher than the potential difference of Pt / C-RuO2 catalyst (ΔE=0.75V). This shows that the bifunctional performance of Fe-NC material is not as good as that of Pt / C-RuO2 catalyst.
[0081] 4) Figure 4 (a) and (b) are the SEM images of the Fe-NC@NiFe-1 catalyst in Example 1 of the present invention and the corresponding backscattered electron scanning electron microscope image (BS-SEM). Through (a) and (b), it can be observed that a large number of NiFe nanoparticles (white bright spots) are evenly distributed on the surface of the carbon particles of the Fe-NC material.
[0082] 5) Figure 5 TEM image (a) and high-resolution TEM image (HR-TEM, b) of the Fe-NC@NiFe-1 catalyst in Example 1 of the present invention; Figure 5 It can be seen that a large number of uniformly sized NiFe particles are evenly distributed on the surface of the Fe-NC carbon particles, and the size of the NiFe nanoparticles is 2 to 5 nm.
[0083] 6) Figure 6 A high-resolution transmission electron microscopy image (HR-TEM) of a single NiFe nanoparticle coated with a carbon layer in the Fe-NC@NiFe-1 catalyst in Example 1 of the present invention; Figure 6It can be seen that the NiFe nanoparticles are covered by a carbon layer with a thickness of about 4-6 carbon atomic layers. The lattice spacing of the NiFe nanoparticles is measured to be about 0.204nm, which is consistent with the lattice spacing of the Ni3Fe(111) plane, confirming that the alloy nanoparticles formed in the Fe-NC@NiFe-1 catalyst are Ni3Fe.
[0084] 7) Comparison of LSV polarization curves of ORR / OER of Fe-NC, Fe-NC@NiFe-1 catalysts prepared in Example 1 and commercial Pt / C-RuO2 catalysts by electrochemical testing (test conditions: in O2 saturated 0.1M KOH solution, rotation speed of 1600rpm, scanning rate of 5mV / s), the results are shown in Figure 7 ;Depend on Figure 7 It can be seen that the potential difference ΔE (E 10,OER -E 1 / 2,ORR ) order is: Fe-NC (1.1V)>Pt / C-RuO2(0.75V)>Fe-NC@NiFe-1(0.66V), indicating that the Fe-NC@NiFe-1 bifunctional catalyst was successfully prepared in Example 1, and its performance was better than that of the commercial Pt / C-RuO2 catalyst.
[0085] 8) Comparison of LSV polarization curves of ORR / OER of Fe-NC@NiFe-2 prepared in Example 2 and commercial Pt / C-RuO2 catalyst by electrochemical testing (test conditions: in O2 saturated 0.1M KOH solution, rotation speed of 1600rpm, scanning rate of 5mV / s), the results are shown in Figure 8 ;Depend on Figure 8 It can be seen that the potential difference of the commercial Pt / C-RuO2 catalyst (ΔE=0.75V) is higher than that of Fe-NC@NiFe-2 (ΔE=0.68V), indicating that Example 2 successfully prepared the Fe-NC@NiFe-2 bifunctional catalyst with better performance than the commercial Pt / C-RuO2 catalyst.
[0086] 9) Comparison of LSV polarization curves of ORR / OER of Fe-NC@NiFe-3 prepared in Example 3 and commercial Pt / C-RuO2 catalyst by electrochemical test (test conditions: in O2 saturated 0.1M KOH solution, rotation speed of 1600rpm, scanning rate of 5mV / s), the results are shown in Fig. 9 ;Depend on Fig. 9It can be seen that the potential difference of the commercial Pt / C-RuO2 catalyst (ΔE=0.75V) is higher than that of Fe-NC@NiFe-3 (ΔE=0.69V), indicating that Example 3 successfully prepared the Fe-NC@NiFe-3 bifunctional catalyst with better performance than the commercial Pt / C-RuO2 catalyst.
[0087] 10) Comparison of LSV polarization curves of ORR / OER of Fe-NC@NiFe-4 prepared in Example 4 and commercial Pt / C-RuO2 catalyst by electrochemical testing (test conditions: in O2 saturated 0.1M KOH solution, rotation speed of 1600rpm, scanning rate of 5mV / s), the results are shown in Fig.10 ;Depend on Fig.10 It can be seen that the potential difference of the commercial Pt / C-RuO2 catalyst (ΔE=0.75V) is slightly lower than that of Fe-NC@NiFe-4 (ΔE=0.76V), indicating that Example 4 successfully prepared the Fe-NC@NiFe-4 bifunctional catalyst with performance similar to that of the commercial Pt / C-RuO2 catalyst.
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst, characterized in that: The following steps are involved: Dimethylimidazole, zinc salt, iron salt and organic solvent are mixed and self-assembled to obtain a transition metal organic framework compound; The transition metal organic framework compound is subjected to heat treatment in a protective atmosphere to obtain a Fe-NC material; The Fe-NC material is physically mixed with an iron precursor and a nickel precursor, and then subjected to microwave heating to obtain a carbon layer-coated NiFe nanoparticle bifunctional composite electrocatalyst.
2. The preparation method according to claim 1, characterized in that: The iron salt includes ferric ammonium sulfate, ferrous sulfate heptahydrate, ferric chloride or ferric chloride hexahydrate; the zinc salt includes zinc nitrate hexahydrate.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the dimethylimidazole, the zinc salt and the iron salt is 30:8:1-5.
4. The preparation method according to claim 3, characterized in that: The temperature of the self-assembly is 20-35° C., and the time is 24-36 hours.
5. The preparation method according to claim 4, characterized in that: The heat treatment temperature is 900-1000° C. and the time is 2-4 hours.
6. The preparation method according to claim 5, characterized in that: The iron precursor includes iron acetylacetonate or iron dodecacarbonyl; the nickel precursor includes nickel acetylacetonate or nickel chloride.
7. The preparation method according to claim 6, characterized in that: The usage ratio of the Fe-NC material, the iron precursor and the nickel precursor is 30-40 mg: 30 mmol: 60-90 mmol.
8. The preparation method according to claim 7, characterized in that: The microwave heating time is 10 to 60 seconds; the microwave heating is carried out under a protective atmosphere, and the gas used in the protective atmosphere includes nitrogen or argon.
9. The carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the carbon layer coated NiFe nanoparticle bifunctional composite electrocatalyst according to claim 9 as a cathode material for metal-air batteries.
Citation Information
Patent Citations
Preparation method of single-atom iron-based oxygen reduction catalyst
CN111952608A
Fuel cell non-noble metal nitrogen-carbon loaded platinum alloy electrocatalyst and preparation method and application thereof
CN115799531A
Monatomic catalyst based on functionalized MOF (Metal Organic Framework) as well as preparation method and application of monatomic catalyst
CN116130686A
ZIF-8-derived Fe-D-N-C oxygen reduction electrocatalyst and preparation method thereof
CN116914157A
Preparation method of nickel-iron alloy and iron monatomic nitrogen-doped carbon ORR / OER bifunctional catalyst
CN117855496A
Cited By
Fe-GC-coated Fe < 0 > catalyst as well as preparation method and application thereof
CN120618502A